Chirally selective growth and extraction of single-wall carbon nanotubes via fullerene nano-peapods - Zhang, Jinying (2013)
Single-wall carbon nanotubes (SWCNTs) grown from C60 and C70 inside SWCNTs with diameters of 1.5 ± 0.1 nm are investigated. The as-produced SWCNTs have been extracted, separated, and characterized. The products from C70 are dominated by (7,6) and (9,4) SWCNTs, whereas those from C60 are dominated by (6,5) SWCNTs.